1981
DOI: 10.1093/jaoac/64.6.1364
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatography with Electron Capture and Mass Spectrometric Detection of Deoxynivalenol in Wheat and Other Grains

Abstract: A method for determining deoxynivalenol (DON) in wheat has been developed in conjunction with an assessment of contamination in Canada. The sample is extracted with methanol-water; the extract is treated with 30% aqueous ammonium sulfate solution and extracted with 4 portions of ethyl acetate. After further cleanup by column chromatography, the sample extract is derivatized with AT-heptafluorobutyrylimidazole, and the DON tris-heptafluorobutyrate is determined by gas-liquid chromatography with electron capture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
4

Year Published

1984
1984
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 0 publications
0
32
0
4
Order By: Relevance
“…14% moisture). The grain was placed in a freezer at -14°C until analyzed for DON concentration by Research Foods of Toronto by the method of Scott et al (12). The grain was ground, and a 50-g subsample was used for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…14% moisture). The grain was placed in a freezer at -14°C until analyzed for DON concentration by Research Foods of Toronto by the method of Scott et al (12). The grain was ground, and a 50-g subsample was used for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…l), a trichothecene mold metabolite with structural similarities to several other toxic products (T-2, HT-2, diacetoxyscirpenol) produced by strains of Fusarium. While the initial analytical data indicated that levels in grain were generally below 1 pprn DON, some samples of wheat and corn exceeded 8.0 ppm [1,2], and this prompted a concerted effort by the Canadian Health Protection Branch to determine the potential human health hazard associated with this toxicologically uncharacterized material.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous procedures are available for measurement of DON level concentration in wheat meal and flour, including those based on thin-layer chromatography (Truckness et al 1984;Fernandez et al 1994), liquid chromatography (Chang et al 1984;Trenholm et al 1985;Rajaklyä et al 1987), gas chromatography (GC) (Terhune et al 1984;Ware et al 1984;Scott et al 1986;Tacke et al 1996), GC with mass spectrometry (Scott et al 1981), and enzyme-linked immunosorbent assay (ELISA) (Casale et al 1988;Usleber et al 1991Usleber et al , 1993Abramson et al 1998). However, these procedures are not adaptable to rapid (<1 min/sample) testing for inspection or process control.…”
mentioning
confidence: 99%